Assessment of cytotoxicity and mutagenicity of exfoliated graphene. (October 2018) - Fujita, Katsuhide; Take, Seiji; Tani, Ryotaro; Maru, Junko; Obara, Sawae; Endoh, Shigehisa
Abstract: Graphene and related materials (GRMs) have unique optical and thermal characteristics and are expected to be adopted for industrial applications. However, there are concerns with respect to their safety to human health. To conduct cytotoxicity and mutagenicity assessments, exfoliated graphene (EGr) dispersed in Tween-20® was diluted in cell culture medium. Rat alveolar macrophage viability significantly decreased after 24 h exposure to 1 and 10 μg/mL EGr. No significant levels of intracellular reactive oxygen species were detected in the 2′, 7′-dichlorodihydrofluorescin diacetate assay after 24 h of exposure to EGr. The levels of the pro-inflammatory cytokines macrophage inflammatory protein-1α, interleukin (IL)-1β, IL-18, macrophage chemoattractant protein-1, and tumor necrosis factor α were significantly higher in cells treated with 10 μg/mL EGr for 24 h than in untreated controls. Transmission electron microscopy confirmed that EGr was present in the cytoplasm of the cells. Many genes were upregulated by EGr treatment, and significantly overrepresented gene ontology categories included the biological processes "response to external stimulus", "response to stress", "cell-cell signaling", "biological adhesion", and "cell proliferation". EGr did not induce genetic mutations in E. coli or cause micronucleus induction in mouse bone marrow cells. The results suggest that EGr cytotoxicity should be carefully considered. Graphical abstract: Highlights: Exfoliated graphene (EGr; 24 h; 10 μg/mL) reduced rat macrophage cell viability. Cellular uptake and high pro-inflammatory cytokine production were observed. Genes involved in inflammatory responses and cell adhesion were upregulated. No significant ROS generation and mutagenesis was observed. EGr should be carefully handled until its respiratory toxicity is determined.